Leveraging Chennai's Complex Governance Network for Addressing the City's Water Woes. (November 2022) - Roy, Parama; Ayyangar, Akshaya
Chennai's governance network plays a critical role in shaping the city's waterscape. Through an urban political ecology (UPE) lens, this article investigates the intersection between water as part of nature and water as shaped by social context, with a focus on existing governance networks. Using a combination of social network analysis and thematic analysis, the article studies data gathered from in-depth semi-structured interviews, workshop discussions with stakeholders, and extensive literature and policy reviews. The analysis reveals a need to reconfigure the urban governance network and the relationships therein to work towards a sustainable future for Chennai's water system. The article concludes by offering policy recommendations to leverage the strengths and weaknesses of the complex inter-agency relations that shape Chennai's current waterscape.